READING COMPREHENSION DIFFICULTIES ENCOUNTERED BY THE FIRST-GRADE STUDENTS OF SMAN 5 PALU - Indah Khairunnisa, Afifah; Usman, Sriati; Wahyudin, Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to identify the difficulties faced by the tenth-grade students of SMAN 5 Palu and the factors causing the students' difficulties in comprehending English reading text. This research is mixed method research. The subject of research was the tenth-grade students of SMAN 5 Palu. The techniques for collecting the data are interviews and tests. The researchers present the data from the difficulties in comprehending English reading text. The result of the research shows that 13, 33% of students have difficulties in understanding to look for the text's central idea, with an incorrect total of 8. Then, 41, 67% of students have difficulties in understanding vocabulary of the text, with the total of incorrect is 25. Then, there are 8, 33% of students who have difficulties in understanding to look for the detail information of the text, with the total incorrect is 5. Next, there are 36, 67% of students who have difficulties in understanding making inferences of the text with the total of incorrect is 22. The factors causing the students difficulties in comprehending English reading text are difficulty in understanding long sentences in the text, lack of interest reading, difficulty in understanding vocabulary, house environment and school environment.